Research and experimental verification of the molecular mechanism of berberine in improving premature ovarian failure based on network pharmacology. Issue 4 (1st April 2022) - Xue, Wu; Xue, Fan; Jia, Tao; Hao, Ai
ABSTRACT: Based on the research methods of network pharmacology, this study analyzed the improvement effect of berberine (BBR) on premature ovarian failure (POF) and its molecular mechanism. Carry out GO and KEGG enrichment analysis by R language to obtain the potential targets and pathways of BBR in the improvement of POF. Use SD rats and ovarian granulosa cells (GCs) for experimental verification. ELISA was used to measure the content of related hormones in the serum, CCK-8 was used to measure cell viability, western blot was used to measure the content of the target protein in the ovaries and GCs, and q-RT-PCR was used to detect the expression of the target genes in the ovaries and GCs. Predicted by network pharmacology: PTEN, AKT1, FoxO1, FasL, and Bim are the targets with the highest relative correlation between BBR and POF. The results of experiments show that the treatment of low and medium doses of BBR can increase the ovarian index of rats; BBR can increase the levels of Estradiol (E2 ) and Anti-Mullerian hormone (AMH) in the serum of rats and reduce the levels of Follicle stimulating hormone (FSH) and Luteinizing hormone (LH). BBR can increase the cell viability of GCs; BBR can inhibit the PTEN/AKT1/FoxO1 signaling pathway and its phosphorylation level and reduce the expression of Fas/FasL and Bim mRNA. Overall, BBR can promote the ovarian to maintain normal hormone levels, protect GCs, and enhance the function of POF. Graphical abstract: uf0001